Patterns of Failure After Neoadjuvant Stereotactic Body Radiation Therapy or Fractionated Chemoradiation in Resectable and Borderline Resectable Pancreatic Cancer. Issue 7 (August 2020) - Barrord, Michelle; Ahmad, Syed; Patel, Sameer; Olowokure, Olugbenga; Sussman, Jeffrey; Smith, Milton; Poreddy, Sampath; Esslinger, Hope; Latif, Tahir; Choe, Kyuran; Kharofa, Jordan
Abstract : Objectives: The goal of this study was to compare outcomes of patients with borderline and resectable pancreatic cancer treated with neoadjuvant stereotactic body radiation therapy (SBRT) versus fractionated chemoradiation. Methods: Patients with borderline or resectable pancreatic cancer treated with neoadjuvant intent between November 2011 and December 2017 were reviewed. The SBRT volume/dose was 33 Gy in 5 fractions to gross tumor plus abutting vessel with or without 25 Gy in 5 fractions to pancreatic head/body and celiac/superior mesenteric artery. Fractionated chemoradiation volume/dose was 50.4 Gy in 28 fractions to gross tumor, superior mesenteric/celiac arteries, and enlarged lymph nodes with concurrent bolus 5-FU, leucovorin, oxaliplatin, irinotecan or gemcitabine/nab-paclitaxel. Failure patterns, local recurrence-free survival (LRFS), progression-free survival (PFS), and overall survival were assessed. Results: Forty-three patients were reviewed (18 SBRTs and 25 fractionated). Among patients who underwent resection, patients treated with fractionated chemoradiation had improved LRFS (12-month LRFS, 86% vs 62%, P = 0.003) and PFS (median PFS, 23 months vs 11 months, P = 0.006) compared with SBRT. There was no difference in overall survival. Conclusions: Stereotactic body radiation therapy may result in inferior LRFS and PFS compared with fractionated chemoradiation, likely because of under coverage of high-risk vascular targets.